Chemistry Education in the ICT Age - Gupta Bhowon, Minu; Jhaumeer-Laulloo, Sabina; Li Kam Wah, Henri; Ramasami, Ponnadurai (Springer Netherlands : Imprint: Springer, 2009)
This volume is a collection of selected papers presented at the 20th International Conference on Chemical Education (ICCE) held in Mauritius from 3rd to 8th August 2008. ICCE is the main conference of the Committee for Chemistry Education of the International Union of Pure and Applied Chemistry (IUPAC) and has adopted the theme "Chemistry in the ICT Age" in line with a worldwide trend in Science and Technology development. The papers in this volume cover topics ranging from fundamental to applied chemistry, such as Arts and Chemistry Education, Biochemistry and Biotechnology, Chemical Education for Development, Chemistry at Secondary Level, Chemistry at Tertiary Level, Chemistry Teacher Education, Chemistry and Society, Chemistry Olympiad, Context Oriented Chemistry, ICT and Chemistry Education, Green Chemistry, Micro Scale Chemistry, Modern Technologies in Chemistry Education, Network for Chemistry and Chemical Engineering Education, Public Understanding of Chemistry, Research in Chemistry Education, Science Education at Elementary Level.